Aprendendo a ser professora: um estudo sobre a socialização profissional de professoras iniciantes no município de Curitiba - Knoblauch, Adriane (2008)
The present work discusses the professional socialization of teachers in the first years of career in the Fundamental Level in the city of Curitiba. Based on the studies of Pierre Bourdieu, professional socialization means the process through which occurs the incorporation of aspects of the habitus of a certain professional group, based on the origin of the agents. The habitus is understood here as the aspects present in the school´s culture which guide actions and behavior in the interior of a professoral group. The purpose if this study was understand the means by which occurs the professional socialization of beginning teachers, because such aspects belong to a major process of formation of the teacher. The final objective was to contribute with the theories of teacher professionalization. Data were collected by the observation of five teachers in the beginning if their career in a school in the outskirts of Curitiba, during planning time, meetings and other groupal activities in the school, so as to accompany their behavior in relation to other teachers. The five teachers were also interviewed so as to try to establish characteristics of their original habitus, considering financial, cultural and social aspects of their families, as well as their school history and the beginning of the career as a teacher. Other personnel of the school were interviewed, so as to learn how the beginning teachers are seen by them. The analysis of the data, subsidized by studies of Bourdieu and Elias, signaled that, in the professional socialization process, three aspects of the relation between the original habitus of the teachers and the internal school dispositions combine: there are dispositions which need to be incorporated, because they are completely new, such as terms by which the new teachers will need to describe their students´ development, which shows their lack of linguistic capital, necessary for teaching; other dispositions were already a part of their habitus, but needed to be adapted because the teachers learned them when they were students themselves; and there are dispositions in the original habitus which were maintained the submission to the superiors in school, the moral of effort, which comes from their vision of work and the ethics of care and tenderness, which comes from their feminine memory. Such adapted, new and maintained dispositions guided the teachers actions in the beginning of their professional life